Analisis Manajemen Pembiayaan Pendidikan dalam Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Nurlisma Nurlisma; Salmiati Salmiati; Sri Rizky Amelia; Mariana Mariana; Ainal Mardiah; Sonny Muhammad Ikhsan Mangkuwinata (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aimed to analyze educational financing management in improving the quality of learning in elementary schools. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that educational financing management, which includes planning, implementation, and evaluation, has been carried out quite effectively. Planning was conducted through participatory School Activity and Budget Planning (RKAS) involving various stakeholders. Implementation was conducted transparently and accountably in accordance with school needs. Evaluation was carried out periodically through financial reports and internal supervision. Effective financial management had a positive impact on learning quality, indicated by improved teacher competence, adequate facilities and infrastructure, varied learning media usage, and improved student learning outcomes. Statistical analysis also revealed a strong and significant relationship between educational financing management and learning quality. Therefore, effective educational financing management is a key factor in improving the quality of learning in elementary schools.